2016
DOI: 10.18632/oncotarget.14130
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent genetic defects on chromosome 5q in myeloid neoplasms

Abstract: BackgroundDeletion of chromosome 5q (del(5q)) is the most common karyotypic abnormality in myeloid neoplasms.Materials and MethodsTo define the pathogenic molecular features associated with del(5q), next–generation sequencing was applied to 133 patients with myeloid neoplasms (MDS; N = 69, MDS/MPN; N = 5, sAML; N = 29, pAML; N = 30) with del(5q) as a sole abnormally or a part of complex karyotype and results were compared to molecular features of patients diploid for chr5.FindingsA number of 5q genes with hapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 35 publications
(42 reference statements)
2
34
0
Order By: Relevance
“…The molecule was originally associated with its responsiveness against MDS patients with a chromosomal aberration of −5q [63], where 50% of patients showed cytogenetic remission [64]. DDX41 does not lie within the commonly deleted region of 5q [65]; however, recently it was shown that MDS patients with DDX41 mutations or low gene expression respond better to treatment with lenalidomide than MDS patients without DDX41 alteration [19]. The mechanism of this benefit is currently unknown.…”
Section: Future Handling and Treatment Of Ddx41-associated Myeloid Mamentioning
confidence: 99%
“…The molecule was originally associated with its responsiveness against MDS patients with a chromosomal aberration of −5q [63], where 50% of patients showed cytogenetic remission [64]. DDX41 does not lie within the commonly deleted region of 5q [65]; however, recently it was shown that MDS patients with DDX41 mutations or low gene expression respond better to treatment with lenalidomide than MDS patients without DDX41 alteration [19]. The mechanism of this benefit is currently unknown.…”
Section: Future Handling and Treatment Of Ddx41-associated Myeloid Mamentioning
confidence: 99%
“…The genes HSPA9 (Mitochondrial 70 kDa heat shock protein (mtHsp70), also known as mortalin) and CD74 are encoded within or near the proximal CDR at chromosome 5q31.2 and 5q32; respectively, with corresponding expression levels consistent with allelic insufficiency in del(5q) MDS . In an HSPA9 murine knockdown model, erythroid precursors, B lymphocytes, and MEP were significantly reduced .…”
Section: Haploinsufficiency Of Hspa9 and Cd74 Results In B Cell Defectmentioning
confidence: 99%
“…The genes HSPA9 (Mitochondrial 70 kDa heat shock protein (mtHsp70), also known as mortalin) and CD74 are encoded within or near the proximal CDR at chromosome 5q31.2 and 5q32; respectively, with corresponding expression levels consistent with allelic insufficiency in del(5q) MDS. 30 In an HSPA9 murine knockdown model, erythroid precursors, B lymphocytes, and MEP were significantly reduced. 31 Another study showed that a heterozygous, single mutant murine model of HSPA9 and HLA class II histocompatibility antigen gamma or invariant chain gene, CD74, displayed reduced bone marrow-derived colony-forming unit-preB (CFU-preB) compared to the wild type, suggesting that heterozygous loss of CD74 and HSPA9 cooperated to induce similar B cell phenotypes that occur in MDS patients with del(5q), although the precise underlying mechanism has not been elucidated.…”
Section: Haploin Sufficien C Y Of Hspa9 a N D Cd74 Re Sults In B Cementioning
confidence: 98%
“…The stop‐gain substitution c.1275T>A (p.Leu377*), causing premature truncation within the RNA recognition and binding domain, falls within the common AML 5q deletion (Figure 1B) and shows increasing variant allele frequency (VAF) in the tumour samples (50%, 83%, 91% and 85% in BM, T1, T2 and T5, respectively). In myeloid neoplasms with 5q deletions, G3BP1 demonstrates haploinsufficiency and is associated with poor survival 12 …”
Section: Figurementioning
confidence: 99%